Answer:
![z=36](https://img.qammunity.org/2020/formulas/mathematics/middle-school/ee7gt8t25maqwvnmpcysfxtzxfnzofa78a.png)
Explanation:
According to the question,
∝
.......(1)
∝
.......(2)
From equation 1,2 let constant of proportionality be
respectively.
⇒
.......(3)
⇒
.......(4)
From the above equations putting 4 into 3,
![x=k1((k2√(z))^3) =k1.k2^3.(√(z))^3](https://img.qammunity.org/2020/formulas/mathematics/middle-school/fmg4w7ckpmz5ojfa6opaoatekpglu5kt6k.png)
Let the new constant to the above equation be
,
![x=k3(√(z))^3](https://img.qammunity.org/2020/formulas/mathematics/middle-school/5tvky3tsyt1d3i27wbiau0m0s8u9xzj1l3.png)
Given,if x=1, when z=4
![1=k3(√(4) )^3=k3(8)](https://img.qammunity.org/2020/formulas/mathematics/middle-school/ht7qbw7gidevciiu2ajdxv83h8yx049akd.png)
⇒
![k3=(1)/(8)](https://img.qammunity.org/2020/formulas/mathematics/middle-school/7d2y5mb42v5od9p6rnuk553dtz6va0l7ub.png)
Now if x=27, then z=?
![27=(1)/(8) (√(z) )^3](https://img.qammunity.org/2020/formulas/mathematics/middle-school/kmyjb0tc2mu24ct4hgm5dtoe7exutrgt4t.png)
⇒
![(√(z) )^3=27(8)](https://img.qammunity.org/2020/formulas/mathematics/middle-school/51krqes10xjvnqes6hcltr8j2276115pkk.png)
⇒
![√(z)=3(2)=6](https://img.qammunity.org/2020/formulas/mathematics/middle-school/eetkzaoq40qbo6ea4ti24sez0u2yosbab1.png)
![z=36](https://img.qammunity.org/2020/formulas/mathematics/middle-school/ee7gt8t25maqwvnmpcysfxtzxfnzofa78a.png)